Intra-Organizational Social Capital and Product Innovation: The Mediating Role of Realized Absorptive Capacity - Ortiz, Beatriz; Donate, Mario J.; Guadamillas, Fátima (Frontiers in Psychology, 2021)
This paper examines the influence on product innovation of factors based on a company’s transformation and exploitation of knowledge gathered from its intra-organizational relationships. Specifically, this paper analyses the influence of intra-organizational social capital (i.e. comprised by structural, relational and cognitive dimensions) on realized absorptive capacity. Moreover, it analyses the mediating role of realized absorptive capacity on the relationship between internal social capital and product innovation. Based on a sample of companies from the Spanish biotechnological and pharmaceutical industries, two hypotheses were tested using a structural equations model and the particle least squares (PLS) technique. The results support both hypotheses, suggesting that the development of strong and tightly-knit links , based on a common understanding and trust among company members lead the firm to develop dynamic capabilities for transforming and exploiting knowledge acquired externally, which fosters innovation based on new product development. Research limitations, implications and future research are also discussed by the authors of the paper.